Solid-fluid interactions for internal cooling in a turbine blade - Loy, Hong Tat (Nanyang Technological University, 2020)
To achieve higher overall efficiency of aircraft engines, turbine blades are subjected to higher temperatures. Thus, more efficient cooling methods are required. The use of ribbed turbulators is one of the technologies for cooling. It induces turbulence in the cooling air to increase heat transferred from the metal. To obtain greater cooling effect, past researches focused on inducing higher levels of turbulence in the cooling air with different rib configurations. These studies showed that the V ribs had excellent heat transfer capability, yet it was never used in turbine blades. This could be due to an overall increased stress concentration of the V rib on creep and fatigue performances. This research is thus focused on (1) building the bridge to translate the heat transfer performance of the V ribs in terms of creep and fatigue performances and (2) coming up with a design that reconciled enhanced heat transfer and structural performances. Through conjugate analysis, Computational Fluid Dynamics (CFD) results showed a ~140K reduction in temperature for the V ribs compared to the straight ribs. The reduced temperature led to improved creep performance, with a 83.2% reduction in creep strain for the V ribs. However, it experienced a 31.2% increase in stress and a 32.8% reduction in fatigue life compared to the straight ribs. To improve structural performance and retain the enhanced heat transfer characteristics, the V with spine configuration was designed. This design achieved a 4.17% reduction in stress level with similar enhanced heat transfer capability, when compared to the V ribs. Further improvements made to this novel design allowed it to achieve a stress level of 901MPa (~9% reduction in stress level compared to V ribs). Overall, the fatigue life of the improved V with spine increased by 20.1% from that of the V ribs. Both enhanced heat transfer and structural performances were achieved through this design.